DAMPAK KEGIATAN TAMBAK UDANG INTENSIF TERHADAP KUALITAS FISIK-KIMIA PERAIRAN BANYUPUTIH KABUPATEN SITUBONDO - Abdul Muqsith (Samakia : Jurnal Ilmu Perikanan, 2014)
The purpose of this study was to determine the impact of waste from shrimp farming activities on the physical-chemical quality of coastal waters. The study was conducted over three months using the survey method. Measurement and water sampling is done directly (in situ) at three stations are: outlet pond; estuary and coastal waters. Water quality analysis conducted qualitative descriptive by comparing the results of water quality measurements the quality standard limits for the life of marine organisms and shrimp farming. The results showed that the activities of shrimp ponds in the study area have an impact high concentration of TSS in coastal waters. The analysis showed the value of TSS concentrations in coastal waters (average 132.6 ± 58.3 ppm) already exceed the quality standard limits for the life of marine organisms and shrimp farming that is 80 ppm. The results also showed that analysts COD concentration in coastal waters (average 85.69 ± 25.80 ppm) also exceeded the water quality standards for the life of marine organisms and shrimp farming activities is 80 ppm. The high concentration of COD allegedly coastal waters from waste chemicals on agricultural activities on land and domestic waste (settlements) around the coastal areas Banyuputih.